Population Density and Temperature Influence the Return on Maternal Investment in Wild House Mice - Gerber, Nina; Auclair, Yannick; König, Barbara; Lindholm, Anna K. (Frontiers in Ecology and Evolution, 2021)
In mammals, reproduction is influenced by sexual competition, temperature and food availability and these factors might be crucial already during early life. Favourable early life environment and high maternal investment are expected to improve survival and reproduction. For example, in mammals, maternal investment via lactation predicts offspring growth. As body mass is often associated with fitness consequences, females have the potential to influence offspring fitness through their level of investment, which might interact with effects of population density and temperature. Here, we investigate the relationship between house mouse (Mus musculus domesticus) pup body mass at day 13 (used as approximation for weaning mass) and individual reproductive parameters, as well as longevity, under natural variation in population density and temperature (as approximation for season). Further, we assessed the extent to which mothers influence the body mass of their offspring until weaning. To do so, we analyzed life data of 384 house mice from a free-living wild commensal population that was not food limited. The mother's contribution accounted for 49% of the variance in pup body mass. Further, we found a complex effect of population density, temperature and maternal investment on life-history traits related to fitness: shorter longevity with increasing pup body mass at day 13, delayed first reproduction of heavier pups when raised at warmer temperatures, and increased lifetime reproductive success for heavier pups at high densities. Our study shows that the effects of maternal investment are not independent of the effects of the environment. It thus highlights the importance of considering ecological conditions in combination with maternal effects to unravel the complexity of pup body mass on fitness measures.